STRATEGI DAYA SAING PENGUMPUL BUAH PEPAYA (Carica papaya L) CALIFORNIA DI KECAMATAN TAMBANG - Rahmat Saputra Sinuraya (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2026)
vThe purpose of this research is to analyse the right strategy for californiapapaya fruit collector in improving competitiveness using the (SWOT) methodsand (AHP) methods. This research uses SWOT analyse and AHP analyse whichincludes internal factor analyse, external factor analysis, SWOT matrix,alternative strategy hierarchy, and hierarchical data processing through to findstrategy priorities for california papaya collecting traders in KecamatanTambang. Analyse using the SWOT method shows 8 alternative strategies.Furthermore, to determine the priority of the strategy, the AHP method is used,which shows 3 priority strategies including establishing cooperation withsuppliers (0.305), establishing cooperation with agricultural cooperatives(0.264), and utilizing social media (0.122). Keywords: SWOT analyse, AHP analyse, collector